Prevalence and risk indicators of peri‐implant diseases in Spain. (5th November 2018) - Rodrigo, Daniel; Sanz‐Sánchez, Ignacio; Figuero, Elena; Llodrá, Juan Carlos; Bravo, Manuel; Caffesse, Raul G.; Vallcorba, Nuria; Guerrero, Adrián; Herrera, David
Abstract: Aim: To evaluate the prevalence of peri‐implant diseases in Spain, as well as the associated risk indicators. Material and Methods: This is a cross‐sectional study using a network of sentinel dentists, who randomly selected 10 patients with implants (placed, at least, 5 years before), which were clinically and radiographically evaluated. Case definitions were established for peri‐implant mucositis [bleeding on probing (BOP) and no bone level ≥2 mm] and peri‐implantitis (BOP plus bone level ≥2 mm). Potential predictor variables, at univariate and multivariate levels, were explored by means of binary logistic regression. Results: A total of 49 sentinel dentists provided complete data from 474 implants in 275 patients. At implant level, prevalences for peri‐implant mucositis and peri‐implantitis were 27% (95% confidence interval [CI] 22–32) and 20% (95% CI: 15–24), respectively, with 17% of implants (14–21) with bone level ≥2 mm without BOP. At patient level, prevalences were 27% (22–32), 24% (19–29) and 18% (13–22), respectively. In the multiple regression analysis, statistically significant associations for peri‐implantitis ( p < 0.10) were found for gender, peri‐implant supportive therapy, implant location, diameter and surface, type of prosthesis and access to interproximal hygiene. Conclusions: In this representative subject sample across Spain, the prevalence of peri‐implant diseases was high (51%).